Pertuzumab for the treatment of metastatic breast cancer. Issue 8 (August 2013) - Langdon, Simon P; Cameron, David A
Approximately 15% of primary breast cancers have amplification/overexpression of the cell surface receptor HER2. Despite the major improvements in survival achieved by the use of adjuvant trastuzumab, many of these patients still develop metastatic disease, and other patients with HER2 overexpressing breast cancer have overt metastases at first diagnosis. There remains therefore a pressing medical need to identify better therapies for these patients. Pertuzumab is a humanized antibody that targets and binds HER2. Although only modestly active against breast cancer when used as a single agent, pertuzumab has demonstrated significant activity when combined with trastuzumab against trastuzumab-resistant and -sensitive disease. Multiple clinical trials are underway to define the optimal use of pertuzumab (combined with either trastuzumab or trastuzumab-DM1) together with a range of cytotoxic agents or endocrine therapy in multiple settings of HER2-overexpressing breast cancer. This article summarizes the use of pertuzumab in the metastatic disease setting.